Electronic Structure Properties of Doped and Imperfect ZnO Sheets - Caliskan, Serkan; Guner, Sadik; Gurbuz, Osman (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
Employing first principles calculations, we examined doped and imperfect ZnO sheets to reveal the electronic structure properties. We mainly investigated the imperfect sheets arising from the host atom vacancies and doped structures where group-III (Al, B, Ga) atoms were substitutionally placed. The energy band gap and electronic behavior were addressed. We revealed and confirmed that group-III dopants and a particular host atom vacancy played an essential role in the electronic structure behavior of a ZnO sheet. We observed that a Zn or O vacancy modified enormously the band gap of a ZnO sheet and that a single dopant in the supercell resulted in semiconductor-metal transition. Zero bias conductance of a group-III doped ZnO sheet was found to be sensitive to any group-III dopant when it replaced the O atom, implying the substantial role of the dopant plus a certain host atom vacancy in the principle electronic feature of a ZnO sheet.
Keywords: Doped ZnO sheet; electronic structure; first Principles; imperfect ZnO sheet; OXIDE THIN-FILMS; ELECTRICAL-PROPERTIES; MAGNETIC-PROPERTIES; OPTICAL-PROPERTIES; HEXAGONAL ZNO; AB-INITIO; TRANSPARENT; AL; 1ST-PRINCIPLES; TEMPERATURE; Engineering; Science & Technology - Other Topics; Materials Science; Physics